Electrodynamic high voltage pulse devices and technologies; Ninth International Symposium on High Voltage Engineering, Graz, Convention Center, August 28 - September 1, 1995; Subject 7 : High voltage applications, environmental technologies, cryogenic insulation, new technologies - Dulzon A. A. Alfred Andreevich (1995, 1995)
В фонде НТБ ТПУ отсутствует